The Implementation of Micro/Nanobubbles (MNBs) Technology to Treat Basin Water as The Primary Water Source for Hydroponics in Greenhouse - Yusuf, Asep; Asdak, Chay; Muhaemin, Mimin; N.P, Sophia Dwiratna; Sugiarto, Anto Tri; Alam, Hilman Syaeful (The University of Lampung, 2024)
The greenhouse plays a pivotal role in creating an ideal environment for hydroponic cultivation. The greenhouse has utilized rainwater and basin water as a source of raw water for hydroponic farming. Presently, the water quality of Leuwi Padjadjaran basin fails to meet the standards required for hydroponics due to its turbidity, sediment content, discoloration, pH levels exceeding 7, and low dissolved oxygen (DO) concentration of 2.2 mg/l. The micro/nanobubbles (MNBs) technology stands as a viable method for water treatment owing to its capacity to bind impurities via radical OH. The application of MNBs for the treatment of basin water involves the use of a hydrodynamic cavitation MNBs generator with a dual-chamber rotating flow nozzle. The parameters evaluated in this research encompass DO concentration, MNBs stability, microbubble size, and the visual response to MNBs application. MNBs treatment was conducted with three different gases: air, oxygen, and ozone. Microbubbles were measured using the particle image velocimetry (PIV) method. The DO concentration reaches 21.6 mg/l when employing oxygen-based MNBs. On the third day post-generation, MNBs stability still maintains DO concentrations above the initial levels. Thus it can be used as hydroponic raw water. Keywords: DO concentration, Greenhouse, Micro/nanobubbles, Water treatment.